Discovery of a novel 4-pyridyl SLC-0111 analog targeting tumor-associated carbonic anhydrase isoform IX through tail-based design approach with potent anticancer activity - Hashem, Hamada; Abdelfattah, Shadwa; Hassan, Hesham M.; Al-Emam, Ahmed; Alqarni, Mohammed; Alotaibi, Ghallab; Radwan, Ibrahim Taha; Kaur, Kirandeep; Rao, Devendra Pratap; Bräse, Stefan; Alkhammash, Abdullah (Frontiers in Chemistry, 2025)
Introduction: Carbonic anhydrase IX (CA IX) is a tumor-associated enzyme involved in cancer progression and survival. Targeting CA IX with selective inhibitors like SLC-0111 has shown therapeutic potential. This study aimed to develop a novel 4-pyridyl analog (Pyr) of SLC-0111 with enhanced anticancer activity.Methods:Pyr was synthesized using a tail-based design and characterized by NMR. Its cytotoxicity was tested against cancer and normal cell lines. CA inhibition, cell cycle effects, apoptosis induction, and protein expression changes were evaluated. Molecular docking and ADMET predictions assessed binding and drug-like properties.Results and Discussion:Pyr showed selective cytotoxicity toward cancer cells and potent CA IX inhibition. It induced G0/G1 arrest, apoptosis, and modulated p53, Bax, and Bcl-2 levels. Docking confirmed strong CA IX binding, and ADMET analysis indicated good oral bioavailability. These results support Pyr as a promising anticancer candidate.